From biodiversity to ESG: evaluating disclosure approaches of companies operating in Indonesia - Senanayake, Maheshika; Putra, Fajar Kristanto Gautama; Gregory, Richard P.; Harymawan, Iman; Rhee, Jay Hyuk; Ok, Yong Sik (Frontiers in Sustainability, 2026)
Biodiversity and Environmental, Social, and Governance (ESG) are becoming critical national interest in Indonesia. This study explores biodiversity and ESG disclosure practices of Indonesian and Korean companies operating in Indonesia, providing a comparative analysis of their performance and disclosure patterns. The sample comprises 70 companies including top 30 Indonesian companies with lowest ESG risk according to Sustainalytics in 2023 and Korean financial firms with highest revenue operating in Indonesia. Two quantitative assessments were conducted: a 5-year biodiversity disclosure analysis (2019–2023) and an ESG performance evaluation for 2023. Findings showed that in biodiversity disclosure, overall awareness of companies was increasing; less significance had been given to biodiversity by most of the companies. The proportion of Indonesian firms publishing sustainability reports increased from 56.7% in 2019 to 96.7% in 2023, but only 7% treated biodiversity as a material topic and 27% aligned with GRI 304 standards on biodiversity. Indonesian companies show a structured approach to ESG, with defined frameworks and long-term planning, yet lack measurable outcomes and extensive third-party validation. Korean companies showed strong ESG standards but faced challenges in establishing clear frameworks and roadmaps. While both sets of companies were engaged in sustainability, Korean firms exhibited relatively lower biodiversity prioritization and ESG integration compared to Indonesian companies. These insights highlighted the importance of integrating biodiversity within ESG strategies to bridge the gap between corporate sustainability commitments and tangible environmental outcomes. This research also showed the need for policy support, including biodiversity-specific guidelines and financial incentives in Indonesia to encourage companies to integrate biodiversity strategically within their ESG goals.